PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN UNTUK MENGIDENTIFIKASI POKOK PIKIRAN DALAM TEKS BACAAN MELALUI PENGGUNAAN METODE SPEED READING PADA SISWA KELAS V SD GMIT AJAOBAKI - Ayu Isabela Kase; Martha Khristina Kota (Journal of Character and ELementary Education, 2022)
This study aims to find out how to improve reading comprehension skills to identify main ideas in reading texts through the use of the speed reading method in fifth grade students of SD GMIT Ajaobaki. This research is a classroom action research consisting of 2 cycles, each cycle consisting of 4 stages, namely planning, implementation, observation and reflection. The subjects in this study were class V which consisted of 28 students. Data collection techniques used are observation, written test, and documentation. The data analysis used by the researcher is descriptive, looking for the percent value of completeness per cycle. Based on the results of the research in cycle I and cycle II, the following data were obtained: KKM in Indonesian subjects was in 70. After using the speed reading method in Indonesian subjects, in the first cycle data were obtained for 7 students who completed (25%) in the ability test. reading comprehension test and 21 students have not completed (75%), while on the reading comprehension test there are 12 students who have completed (42.85%) in the reading ability test and 21 students have not completed (57.14%). In the second cycle, data were obtained from 24 students who completed (85.71%) in the reading ability test and 4 students did not complete (14.28%), while in the reading comprehension test there were 26 students who completed (92.85%) and 2 students have not completed (7.14%). There was an increase in learning outcomes from cycle I to cycle II, namely the reading ability test by 60.71% and the reading comprehension test by 50%. So it can be concluded that the application of the speed reading method can improve the ability to read quickly in fifth grade students of SD GMIT Ajaobaki.